CHATBOT SEBAGAI SOLUSI PEMBELAJARAN MANDIRI UNTUK BAB KIMIA UNSUR: TINJAUAN LITERATUR DAN REKOMENDASI PENGEMBANGAN DENGAN ADDIE - Febri Yantika, Utin (Dharmas Education Journal (DE_Journal), 2023)
National Exam. According to Permendikbud RI Number 37 of 2018, this chapter has core competency achievements that must be met. These include analyzing (C4) for Bloom’s cognitive domain and presenting data (K.5) for Dyer’s psychomotor domain. However, various data indicate that students struggle to achieve these competencies due to the broad and complex scope of the material and the high level of competence required. This article recommends the use of a chatbot  learning media designed with the ADDIE development model. Through a literature study, this article describes how competence can be achieved by constructing knowledge through the stages of assimilation and accommodation obtained at school by learning independently using a chatbot . Self-learning with chatbot  media developed with ADDIE can provide a solution for achieving competency in the elemental chemistry chapter. Chatbots allow for self-learning anytime and anywhere as needed. Knowledge is constructed and reorganized through independent learning experiences, complementing individual requirements and adding meaning to learning. Further research on chatbot  media in improving learning outcomes in the elemental chemistry chapter and independent learning skills in general is recommended.